Measuring efficiency of stations in an airline network: an application of data envelopment analysis - Mad Ithnin Salleh (2005)
This study attempts to provide a mechanism in measuring relative efficiency of selected five airline stations for the year 2004.The objective is achieved by establishing a set of efficiency indicator particularly in the aspect of relative efficiency covering both input and output factor of the stations. In this context, the relative efficiency of five stations in selected continent involved in the study were using non-parametric technique called Data Envelopment Analysis (DEA). The resultsofusing this method to asses the relative efficienciesofall selected fiveairlinestations are then reported. Outcomes are obtained from seven different specifications of output and input. For overall relative efficiency result, three out of five stations were found to be efficient or productive. These three stations can serve as efficient reference set for the relatively inefficient station for potential improvement.